Expanding access to voluntary HIV counselling and testing in the rural communities of Oyo state, Nigeria;- home based approach for improving uptake (2014)
This study assess the impact of home based HIV counselling and testing in expanding access to HIV voluntary counselling and testing in rural Nigeria. The participants of the study were 1, 200 drawn from five constituent wards in Saki town in four streets, in 12 households using multistage sampling techniques. The participants aged 15–55 years. The instrument used for data collection was HIV counselling and testing client intake form. The design adopted for this study was pre-post quasi experimental design. Three research questions and two hypotheses guided this study. Data analysis employed was data analysis employed was Descriptive statistics of percentage, and ratio odd for the research questions raised while Analysis of Covariance (ANCOVA) was utilized for the two research hypotheses formulated. The results of the study indicates that Home based approach had a significant impact for improving uptake of HIV counselling and testing in rural Nigeria. Again, there was a significant reduction in multiple partners (especially among those tested) and reduction in casual partners in intervention group compared with control group.